Prototype composite membranes of partially reduced graphene oxide/TiO2 for photocatalytic ultrafiltration water treatment under visible light - Athanasekou, C.P.; Morales-Torres, S.; V. Likodimos; Romanos, G.E.; Pastrana-Martinez, L.M.; P. Falaras; Faria, J.L.; Figueiredo, J.L.; Silva, A.M.T. (Applied Catalysis B: Environmental, 2014)
A highly efficient hybrid photocatalytic/ultrafiltration process is demonstrated for water purification using visible light. The process relies on the development of partially reduced graphene oxide/TiO2 composite membranes and their incorporation into an innovative water purification device that combines membrane filtration with semiconductor photocatalysis. Composites consisting of graphene oxide sheets decorated with TiO2 nanoparticles were deposited and stabilized into the pores of ultrafiltration mono-channel monoliths using the dip-coating technique. Cross-flow and dead-end filtration experiments were sequentially conducted in dark, under UV and visible light. The membrane surface was irradiated for the elimination of two synthetic azo-dyes, methyl orange and methylene blue, from water solutions. The synergetic effects of graphene oxide on pollutant adsorption and photocatalytic degradation capacity of TiO2 were thoroughly studied, while the influence of the pore size of the monolithic substrate on the deposition morphologies was also elucidated. Moreover, the performance of the novel hybrid process was compared with that of standard nanofiltration with respect to pollutant removal efficiency and energy consumption, providing firm evidence for its economic feasibility and efficiency. © 2014 Elsevier B.V.